The Inherent Benefit of Monetary Unions - Dominik Groll; Tommaso Monacelli (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
The desirability of flexible exchange rates is a central tenet in international macroeconomics. We show that, with forward-looking staggered pricing, this result crucially depends on the monetary authority's ability to commit. Under full commitment, flexible exchange rates generally dominate a monetary union (or fixed exchange rate) regime. Under discretion, this result is overturned: a monetary union dominates flexible exchange rates. By fixing the nominal exchange rate, a benevolent monetary authority finds it welfare improving to tradeoff efficiency in the adjustment of the terms of trade in order to improve on its ability to manage private sector's expectations. Thus, fixed exchange rate-induced inertia in the terms of trade is a cost under commitment, whereas it is a benefit under discretion, for it acts like a commitment device.
Keywords: F33; F41; E52; 330